An adaptive quadratic approximation for structural and topology optimization. (15th April 2015) - Li, Lei; Khandelwal, Kapil
Highlights: A new adaptive quadratic algorithm for structural and topology optimization is proposed. Inconsistent enforcements in diagonal quadratic approximation methods are addressed. Performance of various approximation schemes is evaluated in dual sequential optimization framework. Structural and topology optimization problems are used for evaluating the performance. Numerical results demonstrate effectiveness of AQA over other existing methods. Abstract: In dual sequential methods for structural and topology optimization, approximations based on diagonal quadratic Taylor series expansion methods are frequently used to construct tractable sub-problems. However, when approximating the second-order terms, some inconsistent enforcements are usually employed to ensure the convexity of the approximations (Groenwold et al. (2010)), which may cause convergence problems in the optimization process. In this paper, an adaptive quadratic approximation (AQA) is proposed to improve robustness and convergence performance of the optimization process. Numerical results on representative structural and topology optimization problems show the efficiency of the new proposed method over other existing algorithms.